Analisis sensitivitas pengaruh liter air dan bumbu marinasi pada ayam broiler menggunakan mesin tumbling - Pryanto, Edy; Putra, Andhika; Sinaga, Kurniawan; Purwosiswoyo, Purwosiswoyo (Journal of Pharmaceutical and Sciences, 2023)
Tumbling is a marination method that combines the process of stirring and homogenizing so that the taste of spice from the marinade is optimally distributed into the meat. Based on the advantages of the tumbling machine, which can stabilize the texture and increase the weight of the carcass that has been cut, this can occur well. So, the researchers wanted to measure the amount of remaining spices in the tumbling machine and measure the yield (weight) before and after marinating. The research method used was a completely randomized design method using five treatments. The results obtained in this research for the 10% increase treatment obtained good results for use; for the 10% decrease treatment, the results were not good for use; for the 20% increase treatment, the results were good for use; and for the 20% decrease treatment, the results were not good for use.